2007
DOI: 10.1038/sj.onc.1210675
|View full text |Cite
|
Sign up to set email alerts
|

Expression and sequence analysis of candidates for the 1p36.31 tumor suppressor gene deleted in neuroblastomas

Abstract: Neuroblastomas are characterized by 1p deletions, suggesting that a tumor suppressor gene (TSG) resides in this region. We have mapped the smallest region of deletion (SRD) to a 2 Mb region of 1p36.31 using microsatellite and single nucleotide polymorphisms. We have identified 23 genes in this region, and we have analysed these genes for mutations and RNA expression patterns to identify candidate TSGs. We sequenced the coding exons of these genes in 30 neuroblastoma cell lines. Although rare mutations were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
96
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 34 publications
3
96
1
Order By: Relevance
“…Two genes of the apoptosis pathway, TNFRSF25 and CASP9, are located within the deleted region on 1p35.3-36.31, which is specific for RET/PTC-positive cases from adults. TNFRSF25 is also a candidate tumour suppressor in neuroblastomas (Okawa et al, 2008), whereas CASP9 deregulation has frequently been described in human cancers, for example in gastric carcinomas where it is reported that its activation is inhibited by phosphorylation through the MAP kinase pathway (Yoo et al, 2007). An interesting finding of this study is the deletion of RET because its activated form, RET/PTC, is known as a marker of PTC.…”
Section: Array Cgh On Ptc K Unger Et Almentioning
confidence: 71%
“…Two genes of the apoptosis pathway, TNFRSF25 and CASP9, are located within the deleted region on 1p35.3-36.31, which is specific for RET/PTC-positive cases from adults. TNFRSF25 is also a candidate tumour suppressor in neuroblastomas (Okawa et al, 2008), whereas CASP9 deregulation has frequently been described in human cancers, for example in gastric carcinomas where it is reported that its activation is inhibited by phosphorylation through the MAP kinase pathway (Yoo et al, 2007). An interesting finding of this study is the deletion of RET because its activated form, RET/PTC, is known as a marker of PTC.…”
Section: Array Cgh On Ptc K Unger Et Almentioning
confidence: 71%
“…The recent description in this region of CHD5 as a new tumor suppressor in human cancer threw light on this issue. 40,55 CHD5 appeared as a target shared for miR-1201, miR-1202 and miR-1203. Interestingly, PRDM16, Wnt3 and Hes genes are predicted targets that map into the same region of human chromosome 1p36 and also appear to constitute shared targets for these same novel miRNA (Table 4 and Supplemental Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…101 Expression of CHD5 is very low or absent in neuroblastoma cell lines and is inversely correlated with 1p deletion, MYCN amplification, advanced clinical stage, unfavorable histology, and poor eventfree and overall survival in neuroblastoma tumors. [99][100][101] Homozygous deletion and mutational inactivation of CHD5 are infrequent events, 99 but it has been shown that the remaining CHD5 allele in neuroblastoma cells with heterozygous 1p deletion may be transcriptionally silenced by promoter methylation. 100 Reintroduction of CHD5 in such neuroblastoma cells with 1p deletion and epigenetic CHD5 silencing significantly reduced clonogenicity and in vivo tumorigenicity, validating CHD5 as a bona fide tumor suppressor gene.…”
Section: Transactivation Of Mdm2 Expression By Mycnmentioning
confidence: 99%
“…98 The actual target of this deletion has remained elusive for a long time, but detailed analysis of the different genes located in the smallest region of deletion at 1p36.31 has recently identified CHD5 as the strongest candidate tumor suppressor gene. 99,100 CHD5 encodes a protein with chromatin-organizing modulator (chromo), helicase, and DNA-binding motifs that is preferentially expressed in the nervous system and the adrenal gland. 101 Expression of CHD5 is very low or absent in neuroblastoma cell lines and is inversely correlated with 1p deletion, MYCN amplification, advanced clinical stage, unfavorable histology, and poor eventfree and overall survival in neuroblastoma tumors.…”
Section: Transactivation Of Mdm2 Expression By Mycnmentioning
confidence: 99%